Isotherms, Kinetics and Thermodynamics of 4-Nitrophenol Adsorption on Fiber-Based Activated Carbon from Coconut Husks Prepared Under Optimized Conditions - A. Al-Aoh, Hatem; Jamil Maah, M.; Yahya, Rosiyah; Radzi Bin Abas, M. (Asian Journal of Chemistry, 2013)
A study was carried out to investigate the adsorption of 4-nitrophenol on activated carbon fiber prepared from coconut husk. For comparison, a commercially available granular activated carbon was also tested. The effects of initial concentration, agitation time, solution pH and temperature were examined. Adsorption isotherms were described using the Langmuir and Freundlich models. It was found that, both models fit the experimental data. Pseudo-first-order model, pseudo-second-order model and intra-particle diffusion equations were applied to examine the kinetic data. It was noted that the empirical kinetic data of the prepared activated carbon fiber was well described by the pseudo-second-order model, whereas, the pseudo-first-order model agreed well with the experimental data for the commercial granular activated carbon. Intra-particle diffusion mechanism was partially involved in the case of the commercial adsorbent. It was observed that the prepared adsorbent has both the adsorption capacity and a rate of adsorption higher than that of the commercial one. Adsorption thermodynamic parameters were also estimated. Values of DHº with DSº and DGº indicate that the adsorption of 4-nitrophenol onto both adsorbents are exothermic and spontaneous processes. The DHº values suggest that the adsorption is by chemisorption for the prepared activated carbon fiber and physisorption for the commercial granular activated carbon.